Assessment of passengers satisfaction with bus rapid transit: the case of Dar Es Salaam Rapid Transit (DART) - Mwatawala, Shabani Walad (Department of Civil Engineering, 2020)
This study was carried out in the city of Dar es Salaam, Tanzania, in June 2018. Its main objective was to investigate how the current DART services are delivered with a view of improving urban transport in the city of Dar as Salaam. In all, 260 city residents using DART services were interviewed on their perception of the quality of services on offer. The respondents were selected using the convenience sampling method. A structured questionnaire was used to collect data. The study findings show that the majority of DART users are generally satisfied with services provided. About 96.9 per cent of the interviewed passengers consider continuing using DART services. Service quality attributes, which were perceived with high levels of satisfaction, include security at stations (perceived as adequate by 33.6 per cent and average by 57.8 per cent of interviewed passengers). Another is travel time (88.3 per cent of the passengers were satisfied with the travel time) and shelter (perceived as adequate by 49.6 per cent and average by 38 per cent of the passengers interviewed). The fares charged were reported as affordable by 72.7 per cent of the passengers. Breakdown of buses was reported as a rare occurrence. Critical shortfall perceived by the passengers includes discomfort on the buses due to overcrowding which is a result of too few buses in operation. To reduce congestion, passengers suggested that the number of buses offering the services should be increased. Some 56.8 per cent of the passengers indicated to have failed to arrive at their respective destinations within the planned time. To address this, passengers suggested that timetables should be provided to enable them to plan their journeys and thus arrive within the planned time. Other challenges the passengers faced while using DART services include lack of service when it rains heavily, long queues at ticket booths, and scrambling in the process of boarding the buses. The study findings have not shown a difference in the levels of satisfaction between male and female passengers. Significant difference in the levels of satisfaction has been observed among passengers aged above 45 years in relation to comfort on the buses and the arrival time. Furthermore, the study found that the public was not invited to contribute views on the project. Thus, the public should be invited to contribute their opinions when undertaking future phases of DART. In addition, the current phase of DART should be improved by considering the passengers’ opinions as established by this study.